2013
DOI: 10.1016/j.pharmthera.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Notch inhibitors for cancer treatment

Abstract: Notch signaling is an evolutionarily conserved cell signaling pathway involved in cell fate during development, stem cell renewal and differentiation in postnatal tissues. Roles for Notch in carcinogenesis, in the biology of cancer stem cells and tumor angiogenesis have been reported. These features identify Notch as a potential therapeutic target in oncology. Based on the molecular structure of Notch receptor, Notch ligands and Notch activators, a set of Notch pathway inhibitors have been developed. Most of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
226
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(231 citation statements)
references
References 250 publications
(295 reference statements)
3
226
1
1
Order By: Relevance
“…To 10,11 . L-685,458 strongly inhibits amyloid beta, thus it is widely used in basic research, while DAPT has similar inhibitory effects but needs a greater concentration to inhibit signal peptide peptidase (SPP) 12,13 .…”
Section: Notch Inhibition By Notch Inhibitors (γ-Secretase Inhibitors)mentioning
confidence: 98%
“…To 10,11 . L-685,458 strongly inhibits amyloid beta, thus it is widely used in basic research, while DAPT has similar inhibitory effects but needs a greater concentration to inhibit signal peptide peptidase (SPP) 12,13 .…”
Section: Notch Inhibition By Notch Inhibitors (γ-Secretase Inhibitors)mentioning
confidence: 98%
“…Mice with liver-specific constitutive activation of Notch1 intracellular domain (N1ICD) may develop HCC when they reach adult age (77). Genomic profiling technology has revealed that a Notch-specific gene expression signature reported in mice overexpressing NICD was also present in a cluster of patients with HCC (78). Histological analyses of the mouse liver tissue exhibited similar features compared with that of the HCC patients, which included the presence of proliferating K-19 positive cells.…”
Section: Role Of Notch In Hcc and Icc Developmentmentioning
confidence: 99%
“…gSIs are the most widely studied Notch receptors, having potential for bio-distribution and pan-Notch inhibition (125). gSIs are utilized in Phase I clinical trials as a monotherapy or in combination with other drugs (126). Therefore Notch is a potential antitumor therapeutic target and its implementation should occur subsequent to in-depth study with a focus on the Notch signaling pathway.…”
Section: Targeting Emt-associated Molecules and Pathways In Crcmentioning
confidence: 99%